Microstructure and mechanical properties of Inconel 625/nano-TiB2 composite fabricated by LAAM. (5th December 2016) - Zhang, Baicheng; Bi, Guijun; Wang, Pei; Bai, Jiaming; Chew, Youxiang; Nai, Muiling Sharon
Abstract: Laser aided additive manufacturing (LAAM) was applied to produce nano-TiB2 particle reinforced Inconel 625 composite material. The influence of nano-TiB2 addition on the microstructure, micro-hardness, wear performance and mechanical properties of the composite was studied. The XRD and SEM analyses verified that the LAAM processed Inconel 625/nano-TiB2 composite consisted of single long columnar grain along building direction with TiB2 particles concentration at grain boundaries. The mechanical testing revealed that the LAAM processed Inconel 625/nano-TiB2 composite possessed excellent tensile properties (σUTS  ≈ 1020 MPa, σ0.2YS  ≈ 714 MPa, δ ≈ 19%) with relatively high micro-hardness (HV0.2  = 347) and good abrasive resistance (COF ≈ 0.39). Highlights: Addition of nano-TiB2 to Inconel 625 can lead a single long columnar grain with enforced grain boundary. Excellent mechanical properties of LAAM processed Inconel 625/TiB2 composite has been achieved. Addition of Nano-TiB2 particles leads to the increase of hardness and surface wear resistance.